High-Grade Inflammation Attenuates Chemosensitivity and Confers to Poor Survival of Surgical Stage III CRC Patients - Ying, Hou-Qun; You, Xia-Hong; Liao, Yu-Cui; Sun, Fan; Cheng, Xue-Xin (Frontiers in Oncology, 2021)
Background Heterogeneous clinical and molecular characteristics are reported in colorectal cancer (CRC) with different tumor laterality. However, outcome of left- and right-sided patients with stage I-III CRC and the role of chronic inflammation in survival difference between them remain unclear. Method A retrospective study including 1181 surgical patients with stage I-III CRC was carried out to investigate the involvement of circulating fibrinogen to pre-Alb ratio (FPR) and primary tumor sidedness in clinical outcome of those patients. We further investigated the effect of FPR on adjuvant chemotherapy response and recurrence in stage III patients. Results Our study showed that the right tumor location was significantly associated with poor recurrence-free survival (RFS) (p=0.04, adjusted HR=1.41, 95%CI=1.02- 1.94) and overall survival (OS) (p=0.04, adjusted HR=1.55, 95%CI=1.01-2.38 ) only in the stage III disease. In these patients, T4 stage distribution(p<0.01 for 83.39% vs.70.94%) within right-sided cases was significantly higher than left-sided patients. Moreover, preoperative FPR within right-sidedness(p<0.01), T4 stage(p<0.05) and large cancer bulk(≥5cm)(p<0.05) subgroups was obviously elevated comparing to their counterparts, and it was gradually rising in accordance with the increased cancer bulk(p-trend<0.01). High-FPR distribution (p<0.01 for 52.30% vs. 27.00% ) within right-sided patients with the stage III disease was significantly higher than the left-sided cases. RFS(plog-rank<0.01) and OS (plog-rank<0.01) of the high-FPR patients were extremely inferior to the low-FPR cases, and the significant associations were observed when they were adjusted by other confounders including primary tumor location (p<0.01, adjusted HR=1.96, 95%CI=1.42-2.70 for RFS; p<0.01, adjusted HR=2.44, 95%CI=1.59-3.75 for OS). Additionally, RFS of adjuvant chemotherapy- treated high-FPR patients was superior to the patients without chemotherapy (plog-rank=0.01), but was inferior to the low-FPR patients undergoing the treatment, especially in 5-FU- and XELOX-treated subgroup. Conclusion These findings indicate that chronic high-grade inflammation weakens chemotherapy efficacy and contributes to poor prognosis of stage III surgical CRC patients.